1996
DOI: 10.1002/eji.1830260438
|View full text |Cite
|
Sign up to set email alerts
|

Activity of neutral endopeptidase and aminopeptidase N in mouse thymic stromal cells which bind double‐positive thymocytes

Abstract: The activity of two peptidases was determined in immortalized lines of thymic stromal cells. A line of total stromal cells (T-TG-St) was grown from transgenic mouse expressing temperature-sensitive SV40 T antigen under the control of the regulatory elements of the mouse major histocompatibility complex class I gene. From these cells we isolated a subset (DP-TG-St) that binds thymocytes which are mainly CD4+8+. We also assayed a clone of fetal thymic epithelial cells (BA/10) that binds CD4+8+ thymocytes. Both l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Since membrane CD13 was found neither on immature thymic, nor on mature splenic T lymphocytes (Hansen et al 1993), CD13 mRNA observed in thymus in our study may be due to stromal cells. Namely, Small et al (1996) reported that thymic stromal cell lines, which bind double positive T lymphocytes, express strong APN enzyme activity. The proposed role of APN on stromal cells was contribution to local micro-environment in developing T lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Since membrane CD13 was found neither on immature thymic, nor on mature splenic T lymphocytes (Hansen et al 1993), CD13 mRNA observed in thymus in our study may be due to stromal cells. Namely, Small et al (1996) reported that thymic stromal cell lines, which bind double positive T lymphocytes, express strong APN enzyme activity. The proposed role of APN on stromal cells was contribution to local micro-environment in developing T lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we have studied female mice because none of 49 male mice injected by hydrocortisone acetate at the same dosage survived more than eight injections (Small et al 1989). FACS analysis revealed a trend toward decreased double positives and increased CD4+ single positive cells with aging, as others have reported in mice of more advanced age (Hirokawa et al 1990).…”
Section: Discussionmentioning
confidence: 69%
“…Thymocytes were stained with FITC-CD8 and phycoerythrin (PE)-CD4 (Pharmingen) and analyzed on a FACSort as described previously (Small et al 1996).…”
Section: Facs Analysismentioning
confidence: 99%
“…Cells bearing each ligand were isolated from an immortalized thymic stromal line grown from an adult mouse (Small et al 1996). After preliminary enrichment of the cells that bind the extracellular domain of Notch, cells were treated with an antibody against the amino terminus of Jagged-1 or Delta-1 (followed by FITC-labeled reagents), and strongly fluorescent cells were sorted on the FACS.…”
Section: Resultsmentioning
confidence: 99%
“…Notch ligands could be expressed on lymphoid as well as on stromal cells, and to eliminate nonstromal elements, an immortalized stromal line was used as the source of cells (Small et al 1996). This cell line was grown from an adult (C57Bl · C3H) F 2 transgenic mouse with a temperature-sensitive SV40 T antigen under control of the mouse H-2K b promoter.…”
Section: Cellsmentioning
confidence: 99%